Femoral Deformity May Be More Predictive of Hip Range of Motion Than Severity of Acetabular Disease in Patients With Acetabular Dysplasia: An Analysis of the ANCHOR Cohort. Issue 7 (July 2016) - Fabricant, Peter D.; Sankar, Wudbhav N.; Seeley, Mark A.; Beaulé, Paul E.; Clohisy, John C.; Kim, Young-jo; Millis, Michael B.; Peters, Christopher L.; Podeszwa, David A.; Schoenecker, Perry L.; Sierra, Rafael J.; Sink, Ernest L.; et al.
Abstract : Background: It is generally believed that acetabular dysplasia (AD) is associated with increased hip range of motion (ROM). The purpose of this study was to investigate the associations between dysplasia severity and hip ROM in a large multicenter cohort. Methods: A prospective registry of patients undergoing periacetabular osteotomy for symptomatic AD by 1 of 13 surgeons was used to analyze 1, 051 patients (mean age, 26 ± 10 years). Multivariable linear regression modeling was used to investigate for associations between dysplasia severity (severe, <5°; moderate, 5° to 15°; mild, >15°), α angle, and hip ROM. Results: When controlling for age, sex, body mass index, and α angle, only internal (α = 1.94; P = 0.005) and external (α = −2.63; P < 0.001) rotation in extension were significantly different between groups with increasing dysplasia severity. Alpha angle was greater for those with severe AD compared with subjects with mild disease (60° ± 16° versus 57° ± 15°; P = 0.038). Alpha angle was also significantly correlated with rotational ROM parameters (internal and external rotation in flexion and extension) (Pearson r, range: −0.077 to −0.216; P < 0.05 for all), but not with linear motion. Conclusions: Internal rotation in extension was directly associated with dysplasia severity, whereas external rotation in extension was inversely associated. Furthermore, α angle was greater with increasing dysplasia severity and predictive of rotational ROM parameters. Taken together, these data suggest that femoral-sided deformity, including α angle and possibly femoral version, may be responsible for differences in ROM based on dysplasia severity. Level of Evidence: Level III, Prognostic